THEORETICAL AND EXPERIMENTAL ANALYSIS OF A VAPOR-COMPRESSION REFRIGERATION CYCLE WITH A HEAT EXCHANGER BETWEEN THE SUCTION AND LIQUID LINES - Santana, L. S.; Castro, J.; Pereira, L. M. (Revista de Engenharia Térmica, 2019)
Vapor-compression refrigeration systems require a significant amount of electrical energy. Therefore, there is a need for finding efficient ways of operating this equipment, reducing their energy consumption. The use of heat exchangers between the suction line and the liquid line can produce a better performance of the thermodynamic cycle, as well as reduce it. The present work aims at an experimental analysis of the suction/liquid heat exchanger present in a freezer running with refrigerant fluid R-134a. Three different scenarios were used in order to evaluate the thermal performance of the refrigeration cycle. The first scenario was the conventional freezer set up to collect the required data for further comparison. Moreover, the second and third scenarios were introduced with a 20 cm and 40 cm suction/liquid heat exchanger, respectively, into the system. From the experiments, it was observed that the heat exchange does not significantly affect the coefficient of performance (COP) of the freezer. It was concluded from this work that the best scenario analyzed was the 20 cm suction/liquid heat exchanger where most of the thermodynamic properties were improved, one of them being the isentropic efficiency.